Crystallization‐induced formation of rigid amorphous fraction. Issue 2 (12th September 2018) - Di Lorenzo, Maria Laura; Righetti, Maria Cristina
Abstract: Semicrystalline polymers contain amorphous fractions of different mobility that develop upon crystallization or ordering. The restraints created by the ordered phase, together with the entanglements present in the amorphous areas, set up a disordered nanophase called rigid amorphous fraction (RAF). The RAF is located at the crystal/amorphous boundary and mobilizes at temperatures higher than the glass transition of the mobile amorphous fraction. An updated three‐phase description of semicrystalline polymers is here depicted, with special attention given to the link between RAF vitrification and crystallization kinetics. The methods commonly used to quantify the RAF, and the influence of thermal history and crystal structure/morphology on the RAF, as well as the influence of RAF on materials properties, are presented and discussed in this review. Abstract : An amorphous fraction with reduced mobility develops at the crystal/amorphous boundary during polymer crystallization. The study of the formation of this fraction, named rigid amorphous fraction (RAF), is of fundamental importance for a full comprehension of the crystallization process in semicrystalline polymers. The RAF evolution in semicrystalline polymers depends on the thermal history and is connected also to specific properties of the polymer, for example mobility of the chains and possible polymorphism. The RAF can be estimated during the crystallization process itself, or, most commonly, at completion of the glass transition, thus accounting for the RAF that forms during isothermal or nonisothermal crystallization and the RAF that can develop upon the subsequent cooling down to T g .